Smart scaffolding / Muhammad Afiq Mohd Farid and Nor Azizah Talkis - Mohd Farid, Muhammad Afiq; Talkis, Nor Azizah (2023)
This study concentrates on proposing an innovative idea to solve the problem in scaffolding construction. Scaffolding is a structure that allows work at elevated heights while ensuring user safety. The structure is widely used on construction sites to gain access to elevated and hard-to-reach areas. It is emphasised that key elements affecting the safety of scaffolding, including anchors, supports, platforms, guardrails, and toe- boards, have been considered. Each of these elements was assessed in every scaffold under consideration. Thus, gaining a better understanding of the actual issues is deemed to be important. As for that, review from the previous studies is important in which the problem related to the said issues can be clearly identified. Based on the review, several issues related to the causes of failure in scaffolding have been identified. Therefore, an innovation idea has been proposed as an improvement to solve the identified issues, hence enhancing the quality of scaffolding. The proposed innovation idea involves the creation of a singular scaffolding named “Smart Scaffolding”.